LAYANAN INFORMASI UNTUK MENINGKATKAN PEMAHAMAN BAHAYA STUNTING BAGI IBU - Satrianta, Hengki; Darmawansyah (Musawa: Journal for Gender Studies, 2022)
Stunting is one of the problems that can potentially be experienced by children. This situation is of course not desired by parents, especially mothers. Unfortunately, the understanding of the dangers of stunting is not yet clear for some mothers. For this reason, information services are provided to determine whether information services are able to increase understanding of the dangers of stunting for mothers. This research is an experimental study with a one group pretest-posttest control group design. The population in this study were mothers at the Posyandu Merpati 2, Jatimurni Bekasi city. The sample in this study was drawn purposively with a total of 38 people. Data were collected through the stunting hazard understanding scale. Data were analyzed descriptively and inferentially. The results showed that information services were able to improve understanding of the dangers of stunting for mothers. The implication of the results of this study is that as a type of service in guidance and counseling, the use of information services can be extended to various life settings.